Relationship between serum myo-inositol and peripheral neuropathy in patients with chronic renal failure - TSUJI, HIROYUKI; KANIU, HITOSHI; MIURA, MASAHIRO; NIHEI, HIROSHI; FURUKAWA, KEIICHI; KUZUHARA, KEIHACHIRO; MIMURA, NOBUHIDE; AKAGI, KUNIHIKO; SUZUKI, YOSHIO; UCHIGATA, MASANOBU; HARA, SHIGEKO (Nihon Jinzo Gakkai shi, 1986)
Myo-inositol is a precursor and component of phosphoinositides which is involved in propagation and generation of action potentials as the nerve function. The first stage of catabolism of serum myo-inositol is performed by an oxidase in the renal cortex. During renal insufficiency, the activities of the oxidase decrease to cause retention of myo-inositol in the blood. Experimental rats of hypermyoinositolemia showed delayed MCV in the sciatic nerve. In this study, serum free myo-inositol (S, fm-I) and serum creatinine (S-Cr) levels as well as peripheral nerve conduction velocity (NCV) were measured prior to dialysis in the patients for whom dialysis therapy has recently been instituted or who have been on dialysis for no less than 10-years. As a result, S. fm-I level was clearly high in those with abnormal NCV compared with those with normal NCV in both groups of patients. In the patients for whom dialysis was recently instituted, there was clealy an inverse correlation between S. fm-I and all of NCV measured in both upper and lower extremities. Based on the above, it will not be unreasonable to consider myo-inositol as a metabolic factor in uremic neuropathy and a uremic toxin.